2001
DOI: 10.1046/j.1355-557x.2001.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aflatoxin B1on growth performance, blood components, immune function and histopathological changes in black tiger shrimp (Penaeus monodonFabricius)

Abstract: A¯atoxin B 1 was studied in juvenile black tiger shrimp (Penaeus monodon Fabricius) (1±2 g) to see the effects on growth performance and histopathology, and in adult shrimp (10±12 g) to study the effects on immuno-physiological function, histopathology and a¯atoxin residue. Feeds supplemented with 0, 50, 100, 500, 1000 and 2500 p.p.b. a¯atoxin B 1 were given to test groups for an 8-week period. A¯atoxin B 1 in the diet showed highly negative correlation to average weight, weight gain and survival (r = ± 0.99, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
2
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 13 publications
(13 reference statements)
13
61
2
16
Order By: Relevance
“…The feed conversion efficiency of the shrimp fed with aflatoxin B, diet without the adsorbent was the highest (Table 1). Boonyaratpalin et al (2000) reported that feed conversion efficiency of P. monodon was increased as increasing levels of aflatoxin B,, whereas protein efficiency ratio was decreased with the increase of aflatoxin B, (Table 1) in accordance with Soonngam (2005). The survival rate of shrimp fed with aflatoxin B, diet without the adsorbent was the lowest compared to the other diets (Table 1).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The feed conversion efficiency of the shrimp fed with aflatoxin B, diet without the adsorbent was the highest (Table 1). Boonyaratpalin et al (2000) reported that feed conversion efficiency of P. monodon was increased as increasing levels of aflatoxin B,, whereas protein efficiency ratio was decreased with the increase of aflatoxin B, (Table 1) in accordance with Soonngam (2005). The survival rate of shrimp fed with aflatoxin B, diet without the adsorbent was the lowest compared to the other diets (Table 1).…”
Section: Resultssupporting
confidence: 73%
“…The absence of aflatoxin B, in shrimp tissues after the experiment was attributed to either the low amount of incorporation t o cause retention in the body of the animal or aflatoxin B, conversion to other metabolites which later were excreted by the animal (Chou et al, 1994;Soonngam, 2005). This indicated a very low potential for aflatoxin B, transmission from edible shrimp tissues t o humans as reported earlier (Chou et al, 1994;Boonyaratpalin et al, 2001;Madhu et al, 2004;Soonngam, 2005).…”
Section: Resultssupporting
confidence: 54%
“…BOONYARATPALIN et al (2001) fed ration contaminated with aflatoxin to shrimp, confirming the presence of these toxins in their muscles after four weeks.…”
Section: Resultsmentioning
confidence: 78%
“…When consuming aflatoxin B1 contaminated food, Litopenaeus vannamei and Penaeus stylirostris presented lesions in the hepatopancrea, antennal gland, mandible organ and hematopoietic organs (BINTVIHOK et al, 2003). Levels of 1000 ng / g of aflatoxin B1 also reduces shrimp growth; decreases blood cells, making shrimp more vulnerable to pathogens; causes decrease in lipid deposit by the hepatopancrea cells and reduction of the survival rate (BOONYARATPALIN et al, 2001;GOPINATH & RAJ, 2009, GOPINATH et al, 2012. The objective of this research was to quantify and identify the toxigenic mycobiota and aflatoxins occurrence in feed intended for shrimp cultivated in the coastal area of Piauí, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Otros trabajos reportan concentraciones similares que han demostrado el beneficio de los probióticos (17,18). Sin embargo, se ha detectado que el CTH en crustáceos puede presentar variaciones importantes (19). Además, de que puede ser alterado por estrés, enfermedades y medio ambiente (20)(21)(22) (14).…”
Section: Discussionunclassified